Cytotoxicity and oxidative stress evaluation of Alginate/Cockle Shell powder nanobiocomposite bone scaffold on osteoblast - Nurnadiah Ahmad,; B. Hemabarathy Bharatham,; Zariyantey Abdul Hamid,; Nor Zulaikha Zulkipli, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Biocompatibility and growth of osteoblast on bone scaffolds play an important role towards their therapeutic application. The presence of oxidative stress generated by bone scaffolds highly influences osteoblast growth and its functional performance. In this study in-vitro interaction of developed Alginate/Cockle Shell powder nanobiocomposite bone scaffold on osteoblast with regards to cytotoxicity and oxidative stress are evaluated. Cytotoxicity studies using MTT assays revealed a significant increase in viability of cultured osteoblast in the presences of the scaffold extracts. The growth of osteoblast on the scaffold were not deterred with the presence of any major oxidative stress factors as determined through oxidative stress profile studies using SOD, GSH and ROS assays. The nanobiocomposite scaffold evaluated in this study shows promising use in regards to facilitating osteoblast proliferation, growth and viability.